Scoville Heat Units of Jungle Curry Paste and Sensory Evaluation of Jungle Curry Made of Different Dried Capsicum Varieties Grown along Thai-Myanmar Border - Phadungath, Chanokphat (วารสารวิจัยมหาวิทยาลัยราชภัฏหมู่บ้านจอมบึง สาขามนุษยศาสตร์และสังคมศาสตร์, 2026)
The objective of this research was to utilize and compare different varieties of dried Capsicum (peppers) fruits in Jungle Curry paste (Thai traditional curry paste from forested areas of Thailand). Four different varieties of dried Capsicum were chosen for the study. One of the Capsicum, Yodson (CH 1), belonging to Capsicum annum, obtained from the local fresh market in Ratchaburi. The other three types belonging to Capsicum frutescens, as locally called Karen chili, were obtained from different locations as follows; CH 2 was cultivated and harvested in Huay Muang Village, Ratchaburi Province, CH 3 was cultivated and harvested in Kanchanaburi Province, and CH 4 was cultivated and harvested in the northern region of Thailand. Eight treatments of jungle curry pastes with four different dried Capsicum fruits (CH1, CH2, CH3, and CH4), and two time points during storage (0 and 30 days) were made in triplicate. Scoville heat units (SHU) of jungle curry paste and sensory evaluation of jungle curry were determined. SHUs were measured by electro-chemical method, and capsicinoid were calculated. 9-Point Hedonic scale was used for sensory evaluation. Results indicated that at both 0 and 30 days of curry paste storage, capsaicin and SHU content in jungle curry paste made with Karen chili from Huay Muang, Ratchaburi was significantly highest, followed by jungle curry made with Karen Chili from Kanchanaburi, while jungle curry pastes made of Yonson chili and Karen chili from Northern region had the lowest capsaicin and SHU. Sensory evaluation results of jungle curry indicated no significant differences in odor, pungency, and overall liking, while jungle curry made of Yondson chili had the highest scores in both color and overall taste attributes.